A GIS-based water resources information system: a regional DSS for IWRM [Integrated Water Resources Management] - Abu-Zeid K.; Elbadawy O. (Water saving in Mediterranean agriculture and future research needs [Vol. 2], 2007)
In no other region of the world has water availability played such a dominating role in determining human activities, urban and rural settlement, socio-economic interactions and development, as it did in the Arab region. More than 85 percent of the Arab region is classified as arid and hyper-arid, receiving an average annual rainfall of less than 250 mm. Regional cooperation is a must to confront serious challenges to development of the region. CEDARE's water resources information system (WRIS) was developed at the aim of facilitating accessibility to reliable water resources information on the Arab region. CEDARE WRIS demonstrates the usefulness of integration of remote sensing, GIS and water resources information as a DSS tool for development in the Arab region. It represents an important tool for strategic planning. With an adequate database, GIS can serve as a powerful analytic and decision-making tool for tourism and agricultural development. This DSS tool could help the Arab countries to enhance their water strategies and define their long-term goals within the framework of integrated water resources management (IWRM).
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)